Long-term phenobarbital treatment is effective in working-age patients with epilepsy in rural Northeast China: a 10-year follow-up study - Li, Rongxin; Zhao, Danyang; Li, Nan; Lin, Weihong (Frontiers in Neurology, 2024)
Introduction Effective management of epilepsy in working-age patients is essential to reduce the burden on individuals, families, and communities. This study aimed to assess the long-term efficacy of phenobarbital (PB) in working-age patients with epilepsy in rural Northeast China and identify the risk factors for seizures during treatment. Methods Patients aged 18–65 years diagnosed with convulsive epilepsy in rural areas of Jilin Province between 2010 and 2024 were included, and demographic and clinical data were recorded. Seizure frequency, self-efficacy, adherence, and adverse events (AEs) were assessed monthly. Results Of the 3,568 participants, 288 (8.1%) withdrew from the study and 159 (4.5%) died. During the first year of treatment, 75.2% of patients experienced a ≥50% reduction in seizure frequency compared with baseline (considered as treatment effectiveness); 53.7% of patients were seizure-free. By the tenth year, 97.7% of patients showed treatment effectiveness, and 89.6% were seizure-free. Self-efficacy was improved in 37.8% of patients in the first year and in 72% of patients by the tenth year. The independent risk factors for seizures during treatment were higher baseline seizure frequency [odds ratio (OR) = 1.431, 95% confidence interval (CI): 1.122–1.824], presence of multiple seizure types (OR = 1.367, 95% CI: 1.023–1.826), and poor adherence (OR = 14.806, 95% CI: 3.495–62.725), with significant differences observed in the first, third, and fifth years. The most commonly reported AEs were drowsiness (43.3%), dizziness (25.0%), and headaches (17.0%), most of which were mild and decreased over time. Age at enrollment was the only factor influencing withdrawal (hazard ratio = 0.984, 95% CI: 0.973–0.996, p = 0.010), with a substantial number of patients who withdrew (32.6%) relocating for work. Cardiovascular disease was the primary cause of death, and age at enrollment was the only risk factor (hazard ratio = 1.026, 95% CI: 1.009–1.043, p = 0.002). Discussion Working-age adults with epilepsy demonstrated a favorable response and tolerability to PB monotherapy. Baseline seizure frequency, seizure type, and adherence consistently predicted prognosis throughout the treatment period. Withdrawal was mainly explained by work-related pressures in this age group. Therefore, it is essential to implement interventions that support patient adherence to therapy and maintain stable regimens.